Peppermint oil loaded on recycled paper as an antibacterial label for shrimp freshness. Issue 1 (April 2021) - Yunilawati, R; Handayani, W; Cahyaningtyas, A A; Imawan, C
Abstract: Peppermint oil was one of the essential oils with an antibacterial bioactive component and the potential to be used as an antibacterial label. The purposes of this research were preparing the antibacterial label and evaluate their activity in prolonging the storage of shrimp. Antibacterial label was created by loading the peppermint oil onto the recycled paper as a matrix. Peppermint oil was characterized with Gas Chromatography-Mass Spectrometry (GC-MS) to identified suspected antibacterial activity compounds. The results showed that peppermint oil contains 39.79% of menthol and 35.69% of menthone as the main component. Peppermint oil and antibacterial labels have been screened for Gram-positive bacteria Staphylococcus aureus NBRC 100910 and Gram-negative bacteria Escherichia coli NBRC 100910 using the paper disk diffusion method. Peppermint oil has antibacterial activity in both bacteria, and the label only have antibacterial activity in E. coli NBRC 100910. The antibacterial labels research on prolonging the storage of shrimp shown that the Total Volatile Basic Nitrogen (TVBN) value was lower than without using the label. The results on this study showed recycled paper filled with peppermint oil can be used as an antibacterial label for an active packaging system.